Arctic and boreal ecosystems of western North America as components of the climate system - Chapin, F S 3rd (Global change biology, 2000)
Synthesis of results from several Arctic and boreal research programmes provides evidence for the strong role of high-latitude ecosystems in the climate system. Average surface air temperature has increased 0.3 °C per decade during the twentieth century in the western North American Arctic and boreal forest zones. Precipitation has also increased, but changes in soil moisture are uncertain. Disturbance rates have increased in the boreal forest; for example, there has been a doubling of the area burned in North America in the past 20 years. The disturbance regime in tundra may not have changed. Tundra has a 3-6-fold higher winter albedo than boreal forest, but summer albedo and energy partitioning differ more strongly among ecosystems within either tundra or boreal forest than between these two biomes. This indicates a need to improve our understanding of vegetation dynamics within, as well as between, biomes. If regional surface warming were to continue, changes in albedo and energy absorption would likely act as a positive feedback to regional warming due to earlier melting of snow and, over the long term, the northward movement of treeline. Surface drying and a change in dominance from mosses to vascular plants would also enhance sensible heat flux and regional warming in tundra. In the boreal forest of western North America, deciduous forests have twice the albedo of conifer forests in both winter and summer, 50-80% higher evapotranspiration, and therefore only 30-50% of the sensible heat flux of conifers in summer. Therefore, a warming-induced increase in fire frequency that increased the proportion of deciduous forests in the landscape, would act as a negative feedback to regional warming. Changes in thermokarst and the aerial extent of wetlands, lakes, and ponds would alter high-latitude methane flux. There is currently a wide discrepancy among estimates of the size and direction of CO2 flux between high-latitude ecosystems and the atmosphere. These discrepancies relate more strongly to the approach and assumptions for extrapolation than to inconsistencies in the underlying data. Inverse modelling from atmospheric CO2 concentrations suggests that high latitudes are neutral or net sinks for atmospheric CO2 , whereas field measurements suggest that high latitudes are neutral or a net CO2 source. Both approaches rely on assumptions that are difficult to verify. The most parsimonious explanation of the available data is that drying in tundra and disturbance in boreal forest enhance CO2 efflux. Nevertheless, many areas of both tundra and boreal forests remain net sinks due to regional variation in climate and local variation in topographically determined soil moisture. Improved understanding of the role of high-latitude ecosystems in the climate system requires a concerted research effort that focuses on geographical variation in the processes controlling land-atmosphere exchange, species composition, and ecosystem structure. Future studies must be conducted over a long enough time-period to detect and quantify ecosystem feedbacks